Evaluation of the Friendship Bench’ Circle Kubatana Tose (CKT): an add-on support group intervention – a mixed-methods pilot interventional cohort study protocol - Dixon Chibanda; Charmaine Chitiyo; Jermaine Dambi; Tariro Dee Tunduwani; Beatrice K Shava; Tapiwa Takaona; Thandiwe Mashunye; Lloyd Dzapasi (BMJ Open, 2024)
Introduction Mental disorders are endemic. However, the mental health treatment gap remains high, especially in low-resource settings. Task-shifting is a universally recommended strategy to mitigate the care gap. The Friendship Bench (FB), a task-shifting, low-intensity psychotherapy programme founded in Zimbabwe, is effective in managing anxiety and depression. The FB programme offers clients the choice of joining add-on mental health support groups known as Circle Kubatana Tose (CKT). These groups offer an opportunity for continued psychoeducation, social support and economic strengthening. However, the evidence base for the effectiveness of add-on support groups is sparse. We hypothesise that participation in CKT is associated with increased adherence to treatment regimens, social support and well-being. This mixed-methods prospective cohort study seeks to evaluate the intermediate effects (6-month follow-up) of CKT groups, including process outcome evaluation.Methods and analysis We will recruit participants (N=178) receiving mental healthcare from the FB in Harare primary care clinics. Follow-up assessments will occur at enrolment, 6 weeks, 3 months and 6 months, assessing changes in common mental disorders (depression and anxiety), social support, positive psychological indices (hope and resilience), health-related quality of life, working alliance, economic outcomes (net income) and implementation outcome (feasibility, acceptability/satisfaction and uptake of services). Quantitative data will be analysed using descriptive analysis, bivariate statistics, Cox proportional hazard models and generalised mixed models (maximum likelihood estimation). Qualitative data will be analysed using thematic analysis.Dissemination and ethics Ethical approval was granted by the Medical Research Council of Zimbabwe (MRCZ/A/2427). The findings will inform the potential utility of add-on support groups in the management of anxiety and depression using task-shifting. Dissemination study outcomes will be disseminated in academic journals, social media, conferences and policy briefs.